Training and Support in the Development of Financial Reports Utilising Excel to Enhance the Village Economy - Ahmed Wadin; Atayundin Hamai (Community Service Akseprin Journal, 2025)
Sustainable village development necessitates proficient and transparent economic administration, exemplified as Village-Owned Enterprises (VOE). This project seeks to enhance the quality of financial recording and reporting in the village, which previously employed a manual system. The employed methodology is Project-Based Learning (PBL) for mentoring and teaching, utilising a basic accounting application developed in Microsoft Excel. The help yielded a notable enhancement in the capacity of Village-Owned Enterprises' management to create accurate and methodical reports in compliance with applicable accounting standards. The deployment of this program enhances the efficiency, transparency, and accountability of VOE's financial management while enabling human resources to adapt to the digitalisation of village administration. Challenges, including inadequate technology resources and initial opposition to change, persist; therefore, additional training and continuous mentoring are advised. This study significantly contributes to enhancing independent and competitive village economic governance via the digitisation of VOE financial management